Medicinal Plant Remedies for Dermatological Problems - Thakur, Sweta; Sidhu, M. C. (Current Botany, 2017)
Present study has been undertaken to document the medicinal plants used to take care of various dermatological problems such as cuts, burns, itching, abscesses, allergies etc. in district Mandi of Himachal Pradesh (India). A total of 1000 respondents were contacted to gather this information using a semi structured questionnaire. This study has highlighted the use of 168 species belonging to 148 genera and 67 families for the purpose under consideration. Most of the plants were herbs followed by shrubs, trees, climber and liana. Leaves were the most frequently used plant part. Medicinal preparations include paste, juice, powder etc. It indicates that the respondents have sound knowledge about the medicinal plants and their utility. Keywords: Ethnobotany, Skin problems, Medicinal potential, Plant species, Mandi, Himachal Pradesh.